Efektifitas Model Pembelajaran Osborn Dengan Teknik Brainstorming Pada Mata Kuliah Metode Numerik - Harfin Lanya; Septi Dariyatul Aini (IndoMath: Indonesia Mathematics Education, 2019)
This study aims to determine the students’ learning outcomes, students’ activities and students’ response of Osborn model with the Brainstorming technique using the matlab application in the numerical method subjects, especially in the roots of nonlinear equations material. This research is descriptive research with a qualitative approach. The subjects in this study were 6 students of sixth semester. Data collected are through observation of student activities, test questions and student response sheets. While data analysis techniques are carried out using the mean and percentage formulas. The results showed that at the 1st meeting the mean student activity reached 84,5%, the second meeting reached 95,2%, and the 3rd meeting reached 98,2%. Student learning outcomes are the lowest 81 and the highest is 93.5. While the percentage of student responses 93.3% is very good category. From the results of this study, it can be concluded that Osborn Learning Model with the Brainstorming technique by applying matlab application is effective on student learning outcomes in numerical method subjects.